(untitled) (Medico Legal Update, 2021)
Background: The burden due to the morbidity and mortality of snake bite in India is significantly higher. It is estimated around 1.2 million snakebite deaths (average 58,000/year) has occurred in India from the year 2000 to 2019. However the real burden of snake bite is unknown due to under reporting. This study aims to bring out region specific data on fatal snake bites Results: The study was conducted at the dep of forensic medicine from 2016 to 2020. A total of 75 cases of fatal snake bite cases were autopsied. The number of female cases 39 (52.3) and males were 36 (48.0). The maximum no 52 (69.4%) cases were reported between the months of April to September. The common time for snake bite was in the night 40 (53.3%) followed by the daytime 33 (44.0%). The place of incidence where most of the bites happened was in and around the homes of the victims 46 (61.3) followed by the workplaces 29 (38.7%). The commonest site were the bite mark was noted in the lower limbs 33 (44%) cases. Around 22 (23.9%) cases were seen in age groups of 45 to 59 years and 19 (25.3%) cases in 35 to 44 years. The species of snake in majority of the cases i.e., 65 (86.7%) was unknown. Around 40 (53.3%) cases of kidney samples showed acute tubular followed by congestion. Conclusion: The number of fatal bites were comparatively higher than that of the statistics available. Most of the findings of our study was consistent with the similar studies. The species of snake was largely unknown in this study because new snake species like hump nose pit viper can inflict fatal bites and are difficult to identify. Region specific data on snake bite will reflect the exact volume of snake bites in the country and would largely help in drafting policies to reduce mortality